2022
DOI: 10.20524/aog.2022.0728
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in hospitalizations for acute cholangitis: a nationwide time trend analysis, 2008-2018

Abstract: Background The data on racial epidemiologic trends for acute cholangitis (AC) are scarce. Therefore, we conducted a longitudinal assessment of the racial breakdown of AC-related hospitalizations in the United States (US) over 11 years (2008-2018). Methods Using the National Inpatient Sample, we retrieved adult (>18 years) patients with AC. The adjusted yearly hospitalization rate per 100,000 for each race category was calculated based on the US population estimate for J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Race has been shown to have an impact on the clinical presentation of many diseases, access to certain procedures, and outcomes of these diseases. For example, studies have shown that African Americans have worse outcomes after trauma [4], Asians represent the minority with the most admissions for acute cholangitis [5], and Latinxs and Native Americans have lower odds of undergoing esophagogastroduodenoscopy (EGD) for upper GI bleeding in rural hospitals [6]. Despite an increasing interest in racial differences in upper GI bleeding [7][8][9], the literature is limited on how race affects the etiologies and outcomes of non-variceal upper GI bleeding (NVUGIB).…”
Section: Introductionmentioning
confidence: 99%
“…Race has been shown to have an impact on the clinical presentation of many diseases, access to certain procedures, and outcomes of these diseases. For example, studies have shown that African Americans have worse outcomes after trauma [4], Asians represent the minority with the most admissions for acute cholangitis [5], and Latinxs and Native Americans have lower odds of undergoing esophagogastroduodenoscopy (EGD) for upper GI bleeding in rural hospitals [6]. Despite an increasing interest in racial differences in upper GI bleeding [7][8][9], the literature is limited on how race affects the etiologies and outcomes of non-variceal upper GI bleeding (NVUGIB).…”
Section: Introductionmentioning
confidence: 99%
“…This condition necessitates a sizable number of emergency surgical interventions [8,9]. Distinct from primary biliary cholangitis, the global incidence of AC stands at approximately 8-12 cases per 100,000 individuals annually [10][11][12]. The wide range of AC patients encountered in healthcare systems underscores the importance of discerning the variables affecting disease progression and outcomes.…”
Section: Introductionmentioning
confidence: 99%